The specificity of urban landscape arrangement in the novel 'The City & The City' by China Miéville - A.Yu. Kolesnikov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper analyzes the novel of C. Miéville “The City & the City” (2009), which synthesizes elements of various genres: noir-novel, dystopia, mystery, social novel, etc. The relevance of the study is associated with issues raised in the novel: inter-ethnic communication, political and social identification, and construction of a multicultural society. The purpose of the study is to analyze the time-space organization of urban space in the novel to identify not only the principles of the design of novel space, but also to show how they relate to social and political issues of the novel. In order to fulfill this purpose, the analysis involves the work by Michel Foucault and his followers associated with the development of the concept of heterotopia. The paper provides several examples showing that splitting a single physical space into two mental cities (Besźel and Ul Qoma) described in the novel is ontological, existential. The identity of the characters is manifested not in the places that are associated with a clear understanding of what city they belong to, but in where there is uncertainty – common and intermediate (interstitial) spaces. These common spaces are a kind of heterotopia exposed the serving of the most fundamental things in the world. Important in this regard is the concept of crosshatching, which determines the mental identity of space. C. Miéville shows conventional, cultural status not only of the phenomenon of the border, but of any social or national identity. One of the most important results of the study is that non-traditional literary analysis tools have been used to investigate the literary text specificity. The obtained results can be used not only by academic scholars in the analysis of spatial-temporal organization of a literary text, but also by representatives of other disciplines (particularly, sociology and anthropology) as an example of the analysis of a specific social model (in this sense, the text of the novel can be considered as a mental social or anthropological experiment).